On the endogeneity of the money stock. A rejoinder - GAMBINO, A. (PSL Quarterly Review, 2014)
In this brief rejoinder the author responds David I. Fand’s clarification regarding the classification of the nominal money stock as exogenous or endogenous based on whether or not the variable is controlled by the monetary authorities. JEL: E51, E40